Incubation of Immune Cell Grafts With MAX.16H5 IgG1 Anti-Human CD4 Antibody Prolonged Survival After Hematopoietic Stem Cell Transplantation in a Mouse Model for Fms Like Tyrosine Kinase 3 Positive Acute Myeloid Leukemia - Hilger, Nadja; Mueller, Claudia; Stahl, Lilly; Mueller, Anne M.; Zoennchen, Bianca; Dluczek, Sarah; Halbich, Christoph; Wickenhauser, Claudia; Gerloff, Dennis; Wurm, Alexander A.; Behre, Gerhard; Kretschmer, Anna; et al. (Frontiers in Immunology, 2018)
Despite the constant development of innovative therapeutic options for hematological malignancies, the gold-standard therapy regimen for curative treatment often includes allogeneic hematopoietic stem cell transplantation (HSCT). The graft-versus-leukemia effect (GVL) is one of the main therapeutic goals that arises from HSCT. On the other hand, graft-versus-host disease (GVHD) is still one of the main and most serious complications following allogeneic HSCT. In acute myeloid leukemia (AML), HSCT together with high-dose chemotherapy is used as a treatment option. An aggressive progression of the disease, a decreased response to treatment, and a poor prognosis are connected to internal tandem duplication (ITD) mutations in the FLT3 gene which affects around 30% of AML patients. In this study, C3H/HeN mice received an allogeneic graft together with 32D-FLT3ITD AML cells to induce acute GVHD and GVL. It was examined if pre-incubation of the graft with the anti-human CD4 antibody MAX.16H5 IgG1 prevented the development of GVHD and whether the GVL effect was impaired. Animals receiving grafts pre-incubated with the antibody together with FLT3ITD AML cells survived significantly longer than mice receiving untreated grafts. The MAX.16H5 antibody incubation did not affect the anti-tumor response mediated by allogeneic graft transplantation and the observed prolonged survival may allow an extended application of additional targeted treatment strategies.